The Wind Blows Where It Wishes: Metalepsis and the Gospel of John in Robert Bresson’s A Man Escaped - Schaser, Nicholas J. (Biblical interpretation, 2025)
Robert Bresson’s A Man Escaped (1956) adapts its source material to refashion a French prisoner’s historical escape from Nazi captivity into an extended meditation on the Gospel of John. The film’s French title—Un condamné à mort s’est échappé ou Le vent souffle où il veut ("One Condemned to Death Has Escaped or The Wind Blows Where It Wishes")—takes its secondary designation from John 3:8. Bresson’s cinematic presentation creates ellipses in the viewing experience that require broad familiarity with John’s Gospel and encourage the readerly recollection of Johannine material that lies beyond the explicit citations—a poetic-literary device known as metalepsis. This methodology prompts viewers to recover unstated Gospel text and discover Christological figuration throughout the film. Metaleptic engagement with Bresson’s film vis-à-vis John situates A Man Escaped as a restaging of the Gospel story that highlights its protagonist’s ultimate freedom as an expression of Christian salvation.